(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tara June Winch is a successful contemporary fiction writer from Australia. Winch, an Aboriginal writer, belongs to the Wiradjuri, an Aboriginal community from Australia. The Wiradjuri Aboriginals live in the northern suburb of Wollongong, New South Wales, Sydney, Australia. In her novel The Yield, she depicts the life of Wiradjuri Aboriginals living under colonial supremacy. She documents the brutal colonial practices of separating Aboriginal children from their families.